Let's take another look at the steps to clarify where the distributive property was applied.
- Given: \(- (3x - 2) + 2(x - 3) = -7\)
- Step 1: \(-3x + 2 + 2x - 6 = -7\)
In Step 1, Peter distributes the negative sign in front of the parenthesis containing \(3x - 2\) and also distributes the \(2\) in front of \(x - 3\). Therefore, this is indeed where the distributive property is applied.
- Step 2: \(-3x + 2x + 2 - 6 = -7\) (this is just rearranging terms)
- Step 3: \(-x - 4 = -7\) (combining like terms)
- Step 4: \(-x - 4 + 4 = -7 + 4\) (adding 4 to both sides)
- Step 5: \(-x / -1 = -3 / -1\) (dividing both sides by -1)
Taking this into account, my initial assessment holds true. The correct answer is:
A. from the given to step 1.
Thank you for prompting a reassessment!